Executive Equity Risk-Taking Incentives and Audit Pricing - Chen, Yangyang; Gul, Ferdinand A.; Veeraraghavan, Madhu; Zolotoy, Leon (The Accounting Review, 2015)
ABSTRACT Using a large sample of U.S. firms spanning the period 2000–2010, we document a strong positive association between the sensitivity of CEO compensation portfolio to stock return volatility (vega) and audit fees. We also show that the positive association between vega and audit fees is weaker in the post-Sarbanes-Oxley Act (SOX) period. In supplementary tests, we show that the relation between vega and audit fees is stronger for firms with older CEOs and in firms where the CEO is also chairman of the board. Collectively, our results suggest that audit firms incorporate executive risk-taking incentives in the fees they charge for their services. JEL Classifications: M41; M42; M52.